Sunscreens effectiveness are not altered by concomitant use of moisturizing creams: An ultraviolet reflectance photography study - Leal, Maria; Aguilera-Arjona, José; De-Gálvez-Aranda, María Victoria; Sánchez-Roldán, Cristina; Herrera-Ceballos, Enrique (Willey, 2021)
Background: Sunscreens are widely used to protect the skin against the harmful effects of solar radiation. It is not known whether solar protection factor of a sunscreen is altered by the concomitant use of other cosmetic products. Objectives: The aim of this study was to analyze changes in the protective effect of different commercial and ISO standards sunscreens with high SPF applied shortly before and after application of non-sunscreens galenic formulas type moisturizing creams. Methods: ISO 24444:2019 standard sunscreens, which claimed SPF 16 and 63, as well as 4 different claimed SPF 50 and 50+ commercial sunscreens were prepared and applied in different sequential order to the back of 25 volunteers and compared with different commercial moisturizing formulas. Ultraviolet (UV) reflectance photography followed by image analysis was used to compare untreated skin and skin treated with moisturizing creams alone and combined with sunscreens. Results: The UV reflectance analysis showed no significant changes of the skin color reflectance treated with moisturizing cream compared with untreated skin. Application of the sunscreen formulations were associated with a 35% - 70% decrease in color related to the in vivo expected SPF, indicating significant UV absorption for all sunscreen formulas. All standard and commercial sunscreens showed no significant differences in UV reflection color level when combined with the different moisturizing creams applied before or after the sunscreen. Conclusions: Effectiveness of low- and high-protection sunscreens were not altered by the concomitant use of a moisturizing creams applied shortly before and after the sunscreens.
Keywords: Piel -- Protección; Piel -- Efectos de la radiación; Rayos ultravioletas; Moisturizing formula; Sun protection; Sunscreens; Ultraviolet reflectance photography